Updated checklist of the bats of the biosphere reserve of Pantanos de Centla, Grijalva-Usumacinta basins - García-Morales, Rodrigo (Ecosistemas y Recursos Agropecuarios, 2020)
Bat diversity within Pantanos de Centla Biosphere Reserve (RBPC) is little known. Increasing the understanding and knowledge of this mammal group is important for conservation actions.Because of this, a literature search through national and internationaldatabases was conducted. Bat assemblage at RBPC is composed of36 species, 25 genera, and five families. Three species are listed inthe NOM-059-SEMARNAT-2010. This information provides a baselinefor decision-making to maintain and conserve bats in the Biosphere Reserve of the Pantanos de Centla.